(untitled) (World Science, 2019)
Our article aims to study the pathomorphological manifestations of angio- and neuroretinopathies as a result of chronic exposure to therapeutic doses of opioid analgesics and the possibility of correction of these changes with the help of pentoxifylline at early stages of destructive changes in the layers of the retina. This goal was achieved by using a histological retinal imaging technique. Histological preparations were prepared according to the conventional method using the dyes hematoxylin, eosin, and (azan) in compliance with the method of Heidenhain. The results of the study in the future will allow us to form a pathomorphological base, which can be used for comparative characterization of the dynamics of the growth of pathomorphological changes in the retinal layers during the short and long term exposure to low doses of opioids and the correction of these changes with pentoxifylline at the early and late stages of opioid exposure. The above will further enable us to establish the most optimal time framework for which there is a characteristic set of pathomorphological manifestations of the initial phenomena of angioneuroretinopathy in the layers of the retina, which is best exposed to corrective effects.